Influência do espaçamento interlamelar da perlita nas propriedades mecânicas do aço ABNT – 1080 - Silva, Edson Xavier Batista da (2022)
In eutectoid ABNT - 1080 steels, the heat treatments make it possible to obtain different microstructures, which gives these steels different applications. In this view, there are heat treatments that allow obtaining the pearlitic microstructure, the pearlite consists of the coexistence of two phases composed of alternating lamellae of cementite and ferrite, and the interlamellar spacing of the pearlite is one of those responsible for changes in the properties of steels with pearlitic microstructure. The present work aims to evaluate the influence of interlamellar perlite spacing on the mechanical properties of ABNT - 1080 steel when it is submitted to different heat treatment conditions. For such, it was necessary to perform a computer simulation of the TTA, TTT and TRC curves with the purpose of determining the parameters related to the heat treatments: isothermal and furnace cooling. The microstructural analysis of the samples was conducted with the aid of the Scanning Electron Microscope (SEM). For hardness classification Vickers microhardness (HV) and Rockwell C hardness (HRC) were tested, while the mechanical properties were determined by three-point bending tests. It was observed that the transformation temperature has a great influence on the interlamellar spacing of the pearlite, which in turn, when decreased, causes an increase in the (micro)hardness. Strain and toughness tend to decrease with decreasing interlamellar perlite spacing, while flexural strength increases significantly. Fractography results for all treatment conditions revealed predominant presence of cleavage facets, which indicates occurrence of brittle fracture.